Ab-initio approach to study hydrogen diffusion in 9Cr steels - Ramunni, Viviana Patricia (2012)
We calculate the equilibrium energies and migration barriers of Fe, Cr and H interstitial defects in alpha-FeX (X=Cr). We use the ab-initio electronic structure code, SIESTA, coupled to the monomer method to find activated states (or migration barriers), in order to study atomic defects diffusion. Ab-initio calculations reveal that in the presence of Cr the H migration barriers are higher than in pure a-Fe. On the other hand,our permeation tests on 9%Cr?91%Fe alloys reveal a permeation coefficient 10 times lower and a diffusion coefficient 200 times lower than in pure, annealed iron. Focusing on our experimental results, we explore very simple model of new H trapping sites and possible migration paths that can explain the experimental observations.